A BIBLIOMETRIC ANALYSIS OF SECOND LANGUAGE ACQUISITION BETWEEN 1997 AND 2018. Issue 1 (March 2020) - Zhang, Xian
Abstract: This study used the bibliometric method to examine the field of second language acquisition (SLA) between 1997 and 2018 to provide a systematic overview of the field and to discover major trends in SLA. Based on citation/cocitation information and keywords retrieved from Web of Science, this study performed three types of bibliometric analyses to identify the prominent scholarly documents, authors, research institutions, geographic regions, and research topics that have been highly influential in the field of SLA over the last two decades. The scientific network maps and the keyword analysis revealed a number of significant changes as well as new trends in the field.